State and Leadership in Islam - Dedi Masri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Leadership is a person's ability to influence, mobilize, direct, guide, guide and control human resources under their leadership so that they are willing to work together well in order to achieve the expected goals. Leadership with regard to strategic duties and responsibilities, namely the authority of a leader in making decisions. Islam directs leadership in the context of assertiveness in accepting or rejecting new things, the reasons for making decisions, and the benefits of making these decisions. Likewise, a leader of a state, whether a president, governor, regent or other position, must be able to be accountable to the people he leads, so that when he is assigned the task of leading an institution or organization or even a country, he is able to bear, carry out and be accountable for it. Therefore, what we need to know are the characteristics of the leader, so that we can imitate him or make it easier for us to choose a leader.